Showdown on the desktop. - Predd, P.P (IEEE spectrum)
This paper describes some recent developments in the field of desktop PC software that could have a serious impact on Microsoft Corp.'s stronghold over the market. These include the increasing popularity of the Linux operating system, the introduction of the Mac Mini from Apple Computer Inc., and the growing market share of Firefox open-source browser from Mozilla Foundation.